2014
DOI: 10.3389/fneng.2014.00030
|View full text |Cite
|
Sign up to set email alerts
|

Brain-computer interface-based robotic end effector system for wrist and hand rehabilitation: results of a three-armed randomized controlled trial for chronic stroke

Abstract: The objective of this study was to investigate the efficacy of an Electroencephalography (EEG)-based Motor Imagery (MI) Brain-Computer Interface (BCI) coupled with a Haptic Knob (HK) robot for arm rehabilitation in stroke patients. In this three-arm, single-blind, randomized controlled trial; 21 chronic hemiplegic stroke patients (Fugl-Meyer Motor Assessment (FMMA) score 10–50), recruited after pre-screening for MI BCI ability, were randomly allocated to BCI-HK, HK or Standard Arm Therapy (SAT) groups. All gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
324
4
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 277 publications
(352 citation statements)
references
References 34 publications
18
324
4
6
Order By: Relevance
“…The mean age of the participants ranged from 49.3 ± 12.5 to 67.1 ± 5.51 years. Six studies targeted chronic patients,39, 41, 59, 60, 61, 62 whereas the remaining three studies targeted,42, 63, 64 patients in the subacute phase, with a mean time from stroke approximately ranging from 2 to 4.5 months. In eight out of the nine studies, the BCI relied on the detection of ERD of SMR related to motor imagery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age of the participants ranged from 49.3 ± 12.5 to 67.1 ± 5.51 years. Six studies targeted chronic patients,39, 41, 59, 60, 61, 62 whereas the remaining three studies targeted,42, 63, 64 patients in the subacute phase, with a mean time from stroke approximately ranging from 2 to 4.5 months. In eight out of the nine studies, the BCI relied on the detection of ERD of SMR related to motor imagery.…”
Section: Resultsmentioning
confidence: 99%
“…The nature of the control group differed across studies: sham‐feedback triggered orthosis movement at random instances in four studies,39, 59, 60, 63 one study used conventional therapy,62 one study used robot‐assisted training,41 one study used NMES,64 and one study used motor imagery 42. Ang et al61 reported results of two different control groups: robot only and conventional therapy only. Whenever available, we used the results of control groups undergoing conventional therapy.…”
Section: Resultsmentioning
confidence: 99%
“…The hypothesis is that the afferent signal generated artificially induces central nervous system plasticity because it is in causal association with the cortical activity associated with the intention to move. Several research groups have recently provided evidence that this type of BCI leads to functional improvements in upper limb or hand function (Ang et al 2010;Broetz et al 2010;Cincotti et al 2012;Daly et al 2009;Kasashima-Shindo et al 2015;Li et al 2014;Mukaino et al 2014;Pichiorri et al 2015;Ramos-Murguialday et al 2013;, although others have found no changes (Ang et al 2014;Buch et al 2008) and data are lacking for the use of such a BCI for altering lower limb function (Teo and Chew 2014). These studies report evidence for neuroplasticity, typically inferred from an improved performance of the BCI (Buch et al 2008;Li et al 2014), from alterations in the amplitude (Broetz et al 2010;Cincotti et al 2012;Li et al 2014;Pichiorri et al 2015) or latency ) of the extracted electroencephalographic (EEG) signal, or by functional magnetic resonance imaging (fMRI) .…”
mentioning
confidence: 99%
“…The issue presents 4 reviews Pineda et al, 2014;Priftis, 2014;Rupp, 2014) and 8 experimental studies (Ang et al, 2014;Daly et al, 2014;Ono et al, 2014;Song et al, 2014;Xu et al, 2014;Young et al, 2014a,b,c). It covers studies on five different patient groups: stroke (Ang et al, 2014;Ono et al, 2014;Song et al, 2014;Young et al, 2014a,b,c), spinal cord injury (SCI) (Rupp, 2014;Xu et al, 2014), autism Pineda et al, 2014), cerebral palsy (CP) (Daly et al, 2014) and amyotrophic lateral sclerosis (ALS) (Priftis, 2014). Three different types of BCI are presented: motor imagery, P300 and neurofeedback (operant conditioning).…”
mentioning
confidence: 99%
“…Several experimental studies in this special issue present BCI applications to improve and restore CNP functions (Ang et al, 2014;Ono et al, 2014;Young et al, 2014a,b) while some present basic research papers looking into the effect of BCI training on the cortical activity (Song et al, 2014;Young et al, 2014b,c) or exploring EEG signature characteristic for a certain patient group, such as SCI or CP (Daly et al, 2014;Xu et al, 2014).…”
mentioning
confidence: 99%